THE EFFECT OF ORGANIZATIONAL CULTURE ON EMPLOYEE ENGAGEMENT IN SERVICE INDUSTRIES - Nabila Suci Ramadhani (GREET, 2025)
Organizational culture is widely recognized as a determinant of employee attitudes and behaviors, yet its role in shaping engagement within service industries remains underexplored. This study examines the relationship between organizational culture and employee engagement in hospitality, healthcare, and retail sectors, where service quality depends heavily on frontline employee interactions. Drawing on Hofstede’s cultural dimensions, the Organizational Culture Assessment Instrument (OCAI), and the Utrecht Work Engagement Scale (UWES), the study employed semi-structured interviews and survey-based data collection. A purposive sample of 30 employees was complemented by quantitative responses from 500 participants to ensure both thematic depth and statistical robustness. Data were analyzed using thematic coding, descriptive statistics, and regression analysis. Results reveal a strong positive correlation between organizational culture and engagement (r = .65, p < .01), with culture explaining 42% of the variance in engagement. Recognition and appreciation emerged as the strongest predictor (r = .72), followed by collaboration and open communication (r = .68). Conversely, rigid and hierarchical cultures were negatively associated with engagement (r = –.45). These findings underscore the strategic importance of cultivating supportive and innovative workplace cultures in service industries, where employee commitment directly affects customer satisfaction and organizational outcomes. The study contributes theoretically by identifying recognition and collaboration as critical cultural drivers in service contexts and provides practical recommendations for managers to enhance engagement through recognition systems, leadership development, and feedback mechanisms.